Вы находитесь на странице: 1из 8

# Semblante, Rhea Angelica D.

## The equation of an upward-facing or downward-facing parabola could be

expressed in the form y=a(x-h)2+k. This form is called the vertex or turning point
form because the values of h and k give the coordinates of the vertex (h,k) of the
parabola. That is, h gives the x-coordinate and k gives the y-coordinate of the
vertex. The a in the equation gives us the idea of whether the graph is facing
upward or downward; thus, it tells us that the graph is a reflection over the x-axis.
If a>0, then the parabola is facing upward and, if a<0, then the parabola is facing
downward.

The equation also tells us the vertical or horizontal translations of the graph
based on the parent graph y=x2. The graph is vertically translated k units up if k>0
and k units down if k<0, and it is horizontally translated h units to the right if h>0
and h units to the left if h<0.

Given that the equation of the vertex is y=a(x-h)2+k, and suppose that the
equation of a parabola is y=2(x-3)2+4, it gives us the information that a=2, h=3 and
k=4 giving us the coordinates of the vertex of the equation which is (3,4).
Considering the rules of translation mentioned above, we can say that the graph
of y=2(x-3)2+4 is the graph of y=x2 translated 3 units to the right and 4 units up and
is reflected over the x-axis. Having said that if a>0 the parabola is facing upward,
and a=2 in the equation, we can say that the graph of y=2(x-3)2+4 is facing upward.

Infinite points (x,y) may or may not satisfy the graph of the equation y=a(x-
h)2+k; thus, it tells us that a certain point may or may not be shown in the graph of
the equation and this can be shown or proved in two ways— graphical method and
algebraic method. Say for example, in the equation y=2(x-3)2+4, the point (1,12) is
an example of a point that is on the graph of the equation. Using the algebraic
method, substituting the values of x and y with the values of the point (1,12) will
give you the following:

12=2(1-3)2+4
12=2(-2)2+4

12= 2(4)+4

12=8+4

12=12

Thus, it tells us that point (1, 12) satisfies the equation and is shown in the
graph.

As we have said, if infinite points may satisfy the equation, there are also
infinite points that may not satisfy it. Say for example the point (-2,5), if you
substitute x with -2 and y with -5, it will give you the following:

5=2(-2-3)2+4

5=2(-5)2+4

5=2(25)+4

5=50+4

5=54

Thus, it tells us that point (-2, 5) does not satisfy the equation considering
that 5≠54 and the graph does not pass through it.

Finding the points that may satisfy the graph or equation may be also be as
important as finding the right equation. In finding the right equation of y=a(x-h)2+k,
we cannot always assume that a-value is equal to 1 given the fact that a-value may
be greater or lesser than 0. For example, in the equation y=a(x+1)2+5, where the
vertex is (-1, 5) and say that the point (2, 2) is on the graph, when you substitute x
with 2 and y with 2, the equation will look like 2=a(2+1)2+5, implying that a-value
may be of another value other than 1 because when we substitute it with one, 2
will never equate with 14. Therefore, in order to find a, we must solve for it
accordingly:

2=a(2+1)2+5
2=a(3)2+5

2=9a+5

2-5=9a+5-5

−3 9𝑎
=
9 9

1
𝑎=−
3

Thus, we can say that the equation that can give us the vertex (-1,5) and
1
satisfy the fact that point (2, 2) is on the graph is the equation y=− (x+1)2+5. Based
3

on the equation, we can say that the parabola is facing downward, given that a<0
1
and the graph of y=− 3(x+1)2+5 is the graph of y=x2 translated 1 unit to the left and

## The equation may also be expressed in general form y=ax2+bx+c, where

you will just have to expand the vertex form. The vertex form is y=a(x-h)2+k, and
to derive to the general form, it may be in the following:

Expand the (x-h)2 in the graph and then, derive from it the general form of
the equation.

y=a(x-h)2+k
y=a(x-h)(x-h)+k
y=a(x2-2h+h2)+k
y=ax2-2ah+ah2+k

Where:

## k=c of the general form or the constant or the y-intercept

1
Therefore, we can say that the equation y=− 3(x+1)2+5 may be written in

## general form as follows:

1
y=− 3(x+1)2+5

1
y=− 3(x+1)(x+1)+5

1
y=− 3(x2+2x+1)+5

1 2 1
y=− 3x2− 3x− 3+5

1 2 14
y=− 3x2− 3x+ 3

1 1 2 14
Hence, the general form of equation y=− 3(x+1)2+5 is y=− 3x2− 3x+ 3 .

Finding the equation may depend on what is given, you may be given the
vertex form and a point or the vertex point and the form or a graph with the points.
However, finding the equation will just be similar and easy if you knew that the
vertex form is y=a(x-h)2+k.

For example, we are given the information that the vertex of the graph is (-
1,-4) and it passes through the point (-2, -1). Knowing the vertex form and the
vertex of the graph is (-1,-4), we can substitute h with -1 and k with -4 of the vertex
form giving us the equation y=a(x+1)2-4. Similar with the problem above, in order
to find the value of a that can satisfy the equation showing that point (-2, -1) is on
the graph, we have to solve for it accordingly by substituting the values of x and y
with -2 and -1 respectively, so that we will be able to derive on the right equation
for the parabolic graph.

y=a(x+1)2-4

-1=a(-2+1)2-4

-1=a(-1)2-4

-1=a-4
-1+4=a-4+4

a=3

## After knowing the value of a, we can now substitute it in the equation

y=a(x+1)2-4, to get the right equation that has a vertex of (-1,-4) and passes
through the point (-2,-1), which gives us the equation in vertex or turning point form
as y=3(x+1)2-4. The general form of the equation which is y=3x2+6x-1 may be
derived similar with the process of the prior example.

y=3(x+1)2-4

y=3(x+1)(x+1)-4

y=3(x2+2x+1)-4

y= 3x2+6x+3-4

y=3x2+6x-1

Based on the equation y=3(x+1)2-4, we can say that the parabola is facing
upward considering that a>0, and the graph of y=3(x+1)2-4 is the graph of y=x2
translated 1 unit to the left and 4 units down.

## As we have mentioned, finding the right equation entails keen

understanding on what is given. For example we are given a parabola whose graph
is as follows:
Based on the graph we can say that the vertex is (-2, -3) where h=-2 and
k=-3 and it passes through the point (0, -4), where x=0 and y=-4. After knowing
those facts, we can say that the process in finding the equation is the same as the
process with the prior examples given. We will just have to substitute the values in
the vertex form y=a(x-h)2+k, thus, it shows us the equation -4=a(0+2)2-3. We will
then solve for the value of a:

-4=a(0+2)2-3

-4=a(2)2-3

-4=4a-3

-4+3=4a-3+3

1
a=-4

1
Thus, we can say that the equation of the graph is y=− 4(x+2)2-3 and that
1
the graph of y=− 4(x+2)2-3 is the graph of y=x2 translated 2 units to the left and 3

units down and is reflected over the x-axis. The parabola is facing downward given
that a<0.
The general form is derived in the same manner with the prior example.

1
y=− 4(x+2)2-3

1
y=− 4(x+2)(x+2)-3

1
y=− 4(x2+4x+4)-3

1
y=− 4x2-x-1-3

1
y=− 4x2-x-4

1
Hence, the general form of the equation is y=− 4x2-x-4.

We can conclude that we follow a simple process that holds true for
different sets of equations. First, we have to identify what was asked and then,
identify what are the given facts and information in order for us to find solution to
what is asked. We also have to understand the core concepts of the topics
regarding the equations so that it will be easier for us to derive what is asked from
the given.

With the given set of problems, they correlate with each other given the
fact that they are just derivations of the equation y=x2 and knowing these fact will
make it a lot easier to find the translations, reflections or the transformations of the
equation/graph.